Jogos digitais na educação básica: proposta de curso – MOOC – para fomentar a produção de recursos educacionais abertos - Streb, Vanessa (2023)
I believe that the evolution of society demands the diversification of tools in the teaching process and I understand the association between the use of digital games and Open Educational Resources – OER – as a methodological proposal to expand strategies in Basic Education. Then, I configure as a problem: to what extent can digital games and OER enhance educational practicesin teacher training? Thus, I aim to develop an Open and Massive Online Course - MOOC, as OER, for teachers and others interested in the subject involving the production of digital games focused on narrative, created from the Brazilian platform FazGame. I define as specific objectives: a) increase the technological-pedagogical fluency of the participants; b) encourage the creation of digital games such as OER; c) provide the interactivity of the participants with the materials produced; d) propose the development of digital games focused on narrative; e) encourage the Open Education policy, through the assumptions of OER. The methodology is anchored in the qualitative approach, following the steps: i) bibliographic research; ii) application of a diagnostic questionnaire; iii) elaboration, development and implementation of the course; and iv) evaluation of the MOOC by the participants. The theoretical framework that supports this work is configured in the studies on games by Huizinga (2014; 2017), McGonigal (2017), Coelho and Costa (2016), Alexandre and Peres (2013), Moran (2013), Whitton (2012), Prensky (2012) and Kill (2013); OER concepts are defined by UNESCO (2017) and corroborated by Mazzardo (2018); Costa et al. (2016); Wiley (2014); Reginatto and Algarve (2020); Jacques and Mallmann (2016); and Santos (2015); and the characterization of MOOC presupposes the vision of Inuzuca and Duarte (2012); and Gonçalves and Gonçalves (2015). The course – “OER in Game” – built and published on the online platform Google Sites, it can be used, shared and remixed to be a democratizing knowledge. The creation and availability of the MOOC has the objective of to support teachers, mainly in Basic Education, to comply with the demands of pedagogical practices because currently they are being challenged to keep up with technological advances, considered the space in which most students it is immersed. The evaluation of the course demonstrates that the proposal collaborates with the expansion of dynamic and interactive pedagogical practices, in addition to promoting new opportunities for the dissemination of knowledge. This research is linked to the Research Line Development of Networked Educational Technologies, of the Postgraduate Program in Networked Educational Technologies at the Federal University of Santa Maria.